Opportunistic infections complicating solid organ transplantation with alemtuzumab induction. Issue 5 (26th September 2015) - Helfrich, M.; Ison, M.G.
Abstract Opportunistic infections remain a common complication of solid organ transplantation. Despite significant changes in immunosuppression and infectious diseases prophylaxis, data are limited on the contemporary epidemiology and outcomes of opportunistic infections. Alemtuzumab, a potent lymphocyte‐depleting antibody, has been used with increased frequency in solid organ transplant recipients in the last decade. A literature review was performed to summarize the current understanding of the epidemiology, risk factors, and outcomes of opportunistic infections complicating solid organ transplantation with and without alemtuzumab induction therapy. Areas where data are limited regarding opportunistic infections in solid organ transplantation with alemtuzumab induction are indicated.